The porteño fantasy: Peruvian women writers in the Buenos Aires of fin de siècle - Vicens, María (2018)
Between 1890 and 1910 several Peruvian womenwriters saw in Buenos Aires a chance to reinvent their literary careers, driven by the early interest that the porteño press had shown for their texts. This encouraging panorama, however,would soon contrast with reality: the experiences that Clorinda Matto de Turner, Mercedes Cabello de Carbonera and Carolina Freyre de Jaimes starred in the Argentine capital expose especially the obstacles they encountered in a city in the midst of modernization, as well as the strategies they deployed to readapt their author profiles and participate therefore in the local cultural field.